2021
DOI: 10.1371/journal.pone.0258306
|View full text |Cite
|
Sign up to set email alerts
|

‘No, you should not beat our child because he will become aggressive:’ Applying a multi-method approach to explore intergenerational transmission of parenting practices

Abstract: Background Exploring the cultural context of intergenerational continuity of warm and harsh parenting informs parents motivations to adopt specific parenting behaviours. Objective Parents’ perceptions of being parented in the past and their current parenting as well as adolescents’ perceptions of current parenting were explored applying a multi-method approach. Methods Following written informed consent, a total of 24 interviews with 10 families (dyads of 14 parents and ten adolescents) from Udupi taluk in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Similar results have been found in Eastern cultures as well, for instance, He et al (2020) , in their study on a sample of 192 participants from rural China found that the emotional warmth of one’s parents was significantly associated with caregiver’s warmth, whereas the rejective parenting style of one’s parents was consequently associated with the hostile parenting style of the caregiver toward their children. However, yet another study conducted in southern India with 10 families indicated that although warm parenting was transmitted across generations, the hostile parenting behavior was discontinued in the presence of external social support ( Sekaran et al, 2021 ). Nonetheless, even though some researchers have initiated investigations of intergenerational transmission of parenting (for ex., Honig, 2014 ; Uba and Jain, 2019 ), there exists relatively marginal literature regarding such transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been found in Eastern cultures as well, for instance, He et al (2020) , in their study on a sample of 192 participants from rural China found that the emotional warmth of one’s parents was significantly associated with caregiver’s warmth, whereas the rejective parenting style of one’s parents was consequently associated with the hostile parenting style of the caregiver toward their children. However, yet another study conducted in southern India with 10 families indicated that although warm parenting was transmitted across generations, the hostile parenting behavior was discontinued in the presence of external social support ( Sekaran et al, 2021 ). Nonetheless, even though some researchers have initiated investigations of intergenerational transmission of parenting (for ex., Honig, 2014 ; Uba and Jain, 2019 ), there exists relatively marginal literature regarding such transmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that up to half of all mental health conditions begin during adolescence, and this is a universal phenomenon [2,12,13]. Precursors to emotional and behavioral problems may include immediate influences including the family, parental warmth and control [14][15][16][17], and peer relationships [18,19]. Hostile parenting is considered a risk factor for emotional and behavioral problems, whereas consistent parenting is a protective factor [20].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is sustained by the social learning theory, according to which observing others in their social context is important in moulding one's behaviour, attitudes and emotional reactions. The child's inclinations and moral cognition are established through social learning and is gradually constructed by observations, modelling and consolidation (Chandra Sekaran et al, 2021;Kristjansson, 2004). Thus, socialization can represent a process through which a child acquires standards, values and practices from the society in which he/she was raised, gradually coming to share different aspects of the emotions, cognition and behaviour of the members from that society (Bennett, 2005).…”
Section: Introductionmentioning
confidence: 99%